PENGARUH VARIASI BERAT BADAN TERHADAP KENAIKAN TEMPERATUR TUBUH DAN NILAI SPECIFIC ABSORPTION RATE PADA PEMERIKSAAN MRI BRAIN - Dimas Prakoso; Fatimah; Bagus Abimanyu; Dartini (JRI (Jurnal Radiografer Indonesia), 2018)
Background : MRI brain is a routine examination, after finished examination will felt warm and sweaty on the back. The heat produced by the SAR effect affected by the body weight examined. This research to determine increasing body temperature and SAR value after MRI brain examination based on different body weight. Methods :The kind of this research is experiment. Research has been done at thirteen (13) samples with characteristic as follows : consisted of 3 men and 10 women with variation of body weight 45 kg until 75 kg. Samples had normal body temperature, no abnormalities in the head, and no claustrophobia. Each samples measure body weight and body temperature before MRI examination, then performed examination of MRI brain used brain routine protocol during 19 minutes 49 seconds. After that, measure body temperature again to find the increasing body temperature and saw the SAR value on SAR information. Then analyzed the affection of the variation of body weight and increasing body temperature, and variation of body weight and SAR value. Data were analysed statistically by using Linear Regression test. Results : The results showed that there were significant affection between variation of body weight and increasing body temperature (p value<0,05) significant with very strong influence (R Square=0,889) and negative correlation with equation y=2,098–0,024x.On variation of body weight and SAR value showed that there were significant affection (p value<0,05) with medium influence (R Square=0,596) and positive correlation with equation y=0,214+0,004x. Conclusion : Based on these results indicate thatmore body weight, increase body temperature will decrease due to the fat in people overweight and more body weight, SAR value will increase according the amount of RF exposure required